Reclaiming Colourful Language: The Impact of Linguistic Reclamation on the Cognitive Processing of LGBTQ+ Slurs - Edmondson, Daniel (2022)
This interdisciplinary psycholinguistic and sociolinguistic thesis explores the cognitive processing of slurs, in particular those targeting the LGBTQ+ community. It also seeks to determine whether the phenomenon of linguistic reclamation has any effects on the processing of slurs. Existing research on the processing of taboo language more broadly has identified that taboo words are accessed from the mental lexicon more slowly than non-taboo words, yet are better remembered than non-taboo language after they are encountered. This body of research has also suggested that among other factors, degree of emotional arousal and perceptions of a word’s tabooness are key modulators of both of these effects. However, until now, research into taboo language processing has not at all considered whether these effects are produced for slur words as a specific category of taboo language, nor whether linguistic reclamation might alter arousal responses and tabooness judgements, to the extent that expected taboo language processing effects are no longer produced. The research consisted of five separate studies. The first two studies were preliminary surveys used to identify the most recognisable LGBTQ+ slurs in contemporary British English, gain insights into their use and reclamation, and produce a database of normed emotional, non-emotional, and reclamation behaviour ratings for these words. Two lab experiments followed, in which the lexical accessibility and recall likelihood of LGBTQ+ slurs was compared both to non-taboo negative words, and other taboo words which were not slurs. Comparisons were also made based on participant demographic data, and the normed ratings were used to model explanations of the results. The final study was a pupillometry study which sought to directly measure an impact of linguistic reclamation on physiological arousal responses. Data collection for this final study had to be postponed due to the COVID-19 pandemic, but the design and potential outcomes of the study are comprehensively detailed within this thesis. I found no overall differences between LGBTQ+ slurs and either the taboo or non-taboo word categories in terms of their lexical accessibility. For recallability, LGBTQ+ slurs – like other types of taboo language – were significantly likelier to be recalled than non-taboo words, but were not significantly likelier to be recalled than other examples of taboo language. However, I did find a difference in recall likelihood between LGBTQ+ slurs and taboo words which were not slurs, exclusively among non-heterosexual participants. I also found that participant gender identity and sexual identity were the best overall predictors of lexical accessibility in my experiments, while word length in characters, familiarity, negativity and tabooness were the best predictors of recall likelihood, depending on the specific comparisons being made. Most importantly, I found that in all of my experiments, at least one measure of linguistic reclamation significantly predicted both lexical accessibility and recall likelihood, with increased reclamation associated with better performance in both kinds of processing task. My findings make significant original contributions to both the psycholinguistic and sociolinguistic study of taboo language, slurs, and linguistic reclamation. The research offers comprehensive normed data on LGBTQ+ slurs, quantifiable measures of their reclamation, as well as the first dedicated exploration of the cognitive processing of slurs and the impact of a sociolinguistic phenomenon on the same. To sociolinguistics, the research provides a new and original evidence base for contemporary theory and perspectives on slurs and their reclamation, as well as an indication that participation in a fundamentally political language project can transform both conscious and unconscious responses to language embedded within issues of systemic power, social marginalisation, and hegemony.